Soy protein-based adhesive with superior bonding strength and water resistance by designing densely crosslinking networks. (5th January 2021) - Zeng, Yunchuan; Xu, Pengwu; Yang, Weijun; Chu, Hong; Wang, Wei; Dong, Weifu; Chen, Mingqing; Bai, Huiyu; Ma, Piming
Graphical abstract: Highlights: A soy protein-based adhesive was synthesized via adding a tailor-made crosslinker. The crosslinker with multiple epoxy groups was designed without solvent or catalyst. The adhesives with superior bonding strength and water resistance was prepared. Abstract: The weak bonding strength and poor water resistance of soy protein-based adhesive have limited its application as a non-formaldehyde adhesive in wood manufacturing industry. In this work, a novel soy protein-based adhesive was prepared by introducing a tailor-made crosslinker with multiple epoxy groups and flexible long chains without any solvent or catalyst via a one-pot strategy. The multiple epoxy groups could react with the hydrophilic groups (hydroxyl and amino) on the soy protein molecules to construct densely crosslinking networks, which was proved by the sol–gel results. The crosslinking networks were beneficial to enhancing the bonding strength and water resistance of the adhesive. Consequently, the dry bonding strength and the wet bonding strength were increased from 1.11 MPa and 0.22 MPa to 2.79 MPa and 1.12 MPa, respectively, marking increments of 151% and 409% when compared to the pristine soy protein-based adhesive. The bonding strength was beyond the standard of type II plywood (≥0.7 MPa, GB/T17657 − 2013). Furthermore, the flexible long chains of the crosslinker was also conductive to improving the toughness of the adhesive. Therefore, this work may open a feasible way to produce non-formaldehyde adhesives with superior bonding strength and water resistance, and thus broadening the application of soy protein.